PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP TINGKAT PENYESUAIAN DIRI SISWA KELAS X SMK KEHUTANAN NEGERI PEKANBARU TAHUN AJARAN 2014/2015 - Kasri Wahyuni Kasri Wahyuni; Zulfan Saam Zulfan Saam; Elni Yakub Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is entitled “the effect of group counseling toward the self adjustment level of the tenth grade forestry vocational school of pekanbaru in 2014/2015 academic year. It is aimed at 1) finding out the level of self adjustment of the tenth grade students before the group counseling was implemented. 2) finding out the ongoing implementation process of counseling the tenth grade students. 3) finding out the level of self adjustment of the tenth grade students after the group counseling was implemented. 4) finding out the differences between pre-implemetation and post-implementation of group counseling toward tenth grade students’ self adjustment level. 5) finding out whether there is an effect of group counseling toward tenth grade students’ self adjustment level. The research subjects are 100 students of the tenth grade of forestry vocational school of pekanbaru. 30% of the population that is equal to 30 persons were taken as samples by using random sampling. As a description of students’ self adjustment level before the implemetation of group counseling, most of them are categorized as unfavorable, a small portion of the students are categorized as very unfavorable, and none of them are categorized as pretty good, good, and very good. While, as a description of post-implemetation of group counseling, the students’ self adjustment level are 16,67% categorized as good, mostly 83,33% are categorized as very good, and none of them are categorized as very unfavorable, pretty unfavorable, and very unfavorable. Based on the hypothesis result test, it shoes that there is significant effect of group discussion toward students’ self adjustment which is amounted to 48%.Keywords: Group Counseling and Self-Adjustment.